2018
DOI: 10.3390/su10051511
|View full text |Cite
|
Sign up to set email alerts
|

Household Energy Expenditures in North Carolina: A Geographically Weighted Regression Approach

Abstract: The U.S. household (HH) energy consumption is responsible for approximately 20% of annual global GHG emissions. Identifying the key factors influencing HH energy consumption is a major goal of policy makers to achieve energy sustainability. Although various explanatory factors have been examined, empirical evidence is inconclusive. Most studies are either aspatial in nature or neglect the spatial non-stationarity in data. Our study examines spatial variation of the key factors associated with HH energy expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
(168 reference statements)
1
10
0
Order By: Relevance
“…The best bandwidth should fall between these two situations [63][64][65]. Methods for bandwidth determination include cross validation (CV), Akaike's information criterion (AIC), Akaike's information criterion corrected (AICc), and BIC/MDL [66,67]. This paper determined the bandwidth by using AICc method.…”
Section: Ols and Gwr Methodsmentioning
confidence: 99%
“…The best bandwidth should fall between these two situations [63][64][65]. Methods for bandwidth determination include cross validation (CV), Akaike's information criterion (AIC), Akaike's information criterion corrected (AICc), and BIC/MDL [66,67]. This paper determined the bandwidth by using AICc method.…”
Section: Ols and Gwr Methodsmentioning
confidence: 99%
“…An analysis of the carbon emissions related to HEC in north-west China conclude that the determinants of pollution vary from one region to another: ''income indicates a greater influence,'' for instance, ''in northern Ningxia and northern Shaanxi'' (Li et al 2016, p. 183). A study on HEC in California (Sultana et al 2018) estimated that the aging of the population has a significant impact on increasing HEC in north-eastern areas, whereas no significant effect is expected in the north-western areas. Two studies on HEC in the Randstad region in the Netherlands show that building age, as a proxy for buildings' energy efficiency, has a greater impact in rural areas than in urban areas (Mashhoodi 2018), and the main determinant of households' gas consumption-i.e.…”
Section: Previous Studies On Local and Global Determinants Of Househomentioning
confidence: 99%
“…Likewise, Oxfam [33] has estimated that the total share of CO 2 emissions from the top 10% of high-income people is approximately 50%. Previous literature for the UK [17][18][19][20] and other countries [21][22][23][24][25][26][27][35][36][37][38] has shown that household emissions are related to a variety of socioeconomic factors and dwelling-related characteristics. For example, there exist a negative link between CO 2 emissions per capita and household size (the number of people in a household), and a positive link between CO 2 emissions per household and household size [21][22][23].…”
Section: Previous Work On Socioeconomic Factors and Household Energy mentioning
confidence: 99%
“…In particular, the household income, age of householders, and category of dwelling have been identified as the main influencing factors on household energy expenditure in North Carolina in the US [38]. Likewise in the UK, Palmer et al [29] have focused only on electricity consumption among households excluding electric heating and electric showers, where it is found that 85% of the high electricity-consuming households in their study (39 out of 46 households that belong to the top 20% high-electricity users) have at least one key contributing factor that could lead to their higher electricity consumption.…”
Section: Previous Work On Socioeconomic Factors and Household Energy mentioning
confidence: 99%